Review of automated writing evaluation systems - Zhang Shuai (Journal of China Computer-Assisted Language Learning)
This review generally endeavours to include a brief description of widely used automated writing evaluation systems, an explanation of underlying technologies, working principles and scopes of application, followed by a critical evaluation of the advantages and disadvantages in using these systems in educational contexts. Hopefully, the review would provide implications for language assessment practice and relevant research.